Anthologies and readers in the 16th century in Portugal: Accounts from André Rodrigues Eborense (1498-1573) and Jorge Ferreira de Vasconcelos (1515?-1585). - Laureano Santos, Maria do Rosário (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Anthologies and readers in the 16th century in Portugal: Accounts from André Rodrigues Eborense (1498-1573) and Jorge Ferreira de Vasconcelos (1515?-1585). The anthologies have remained in Western culture from the Antiquity to the present day. In the Middle Ages, the maxims and sententiae of the Greek and Latin authors were compiled into anthologies, which have circulated among the clergy, in the court, or in the universities. After the removal from their original context, the maxims were grouped into new thematic organizations and have gained a broader and universal sense. In the 16th century, the anthologies, that could have an individual or collective use, were books used for reading or just for consulting within different purposes, whether for personal enjoyment, for schooling, or yet to help the writer in his function. In this paper, our aim is to reflect on the use of the anthologies of two Portuguese authors of the 16th century: André Rodrigues Eborense (1498-1573) and Jorge Ferreira de Vasconcelos (1515?-1585).